The virtuous circle (Volume 7) - MacArthur, Ellen (European Investment Bank, 2019)
Imagine an economy in which today's goods become tomorrow's resources and nothing is discarded. Ellen MacArthur, the founder of her eponymous foundation, which works to accelerate the transition to a regenerative economy, writes that we need to stop living a "take, make, dispose" lifestyle. We need to think about a circular economy where waste and pollution are prevented, products are reused and natural systems such as agricultural land are regenerated. The benefits to cities and countries are huge, as sustainability brings big savings for the environment, mobility, nutrition, textiles, electronics, etc. Businesses, governments, NGOs, and investors have started taking action to make the circular economy happen, and the number of countries and cities drawing up circular economy strategies is multiplying. We now need people with the ability to do so to grasp with both hands the opportunities to design a world that works in the long term. This is the seventh essay in the Big Ideas series created by the European Investment Bank. The EIB has invited international thought leaders to write about the most important issues of the day. These essays are a reminder that we need new thinking to protect the environment, promote equality and improve people's lives around the globe.